Släntstabilitet för sluttäckningen av avfallsdeponin i Holkesmossen, Hagfors kommun : Stabilitetsberäkningar och rekommendationer för fortsatta arbeten - Engström, Tobias (2013)
Holkesmossen recycling station is situated about two kilometers east of the town of Hagfors in Värmland, Sweden. Landfill operations started at the site during the 1960’s, and are still ongoing.In earlier research projects at Luleå University of Technology, together with the municipality of Hagfors and Uddeholms AB, designs for a final cover of the landfill has been developed. In the chosen solution, a mixture of virgin soil materials and alternative materials from the steelworks in Uddeholm are used.In 2005, constructions of a final cover for the landfill begun. Until now, only parts of the north slope has been covered – and constructions are still ongoing in this area. The construction speed is limited by the rate of which the steelworks can produce new materials.In this report, the slope stability of the final cover design at the site has been evaluated. Calculations has been carried out with the FEM-program PLAXIS.To verify the PLAXIS output, the Bishops method and the Morgenstern-Price method were used. These are methods of slices, and were calculated in the software Slope/W.To determine mechanical properties for the waterproofing core material, shear tests were carried out at Luleå University of Technology. Additional laboratory work was carried out in form of a sieve curve for the protection layer, which is made up of 80 % silty till and 20 % sewage slag and bio ash. Additional material parameters and properties were derived from literature.For the slope stability evaluation, a drained analysis was carried out. The results showed that the ground water table has a big influence on the slope stability, especially when considering circular slip surfaces. Because the level of the ground water table is yet to be established, the simulation results were presented as design scenarios based on slope angles and ground water table levels. Additional scenarios, where the strength of the protective layer was lowered, are also included since they instead can produce a transversal slip surface. The factor of safety ...